A scientometric research of high-cited publications in Obsessive-Compulsive Disorders during 2012-2021 - Grover, Sandeep; Gupta, B.M.; Ahmed, K.K. Mueen; Kappi, Mallikarjun (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. To examine the bibliometric characteristics of high-cited publications (HCPs) on Obsessive-Compulsive Disorder (OCD). Design/Methodology/Approach. The Scopus database was searched to identify HCPs on OCD published from 2002 to 2021. Three-hundred and ninety-five (n=395) articles having at least 100 citations were included in the analysis. Quantitative and qualitative indicators were applied to measure and evaluate the research productivity and citation impact of authors from the most productive countries, organizations, and authors. The VOSviewer was used to visualize the collaborative interaction among the most productive countries, organizations, authors, and keywords. Results/Discussion. The 395 HCPs published on OCD during 2012-2021 were cited 75197 times. The authors from the United States (n = 216), United Kingdom (n = 59), Netherlands (n =37), and Canada (n=30) were the most productive. Clinical studies accounted for the largest publications share among publication types, followed by studies focusing on treatment, epidemiology, genetics, risk factors, pathophysiology, and complications. Among important keywords besides OCD, other most common keywords were anxiety (n=89), Cognitive Behavioural Therapy (n=87), Clomipramine (n=68), Fluoxetine (n=65), and Behavioural Therapy (n=53). The topmost productive organizations were the Harvard Medical School, USA (n=37), Massachusetts General Hospital, USA (n=36), Columbus University, USA (n-28), and New York State Psychiatric Institute, USA (n=27). The most productive authors were D. Mataix-Cols (Sweden)(n=21), followed by B.D. Greenberg (USA)(n=18), S.L. Rauch (USA)(n=17) and D.J. Stein (South Africa)(n=17). These 395 HCPs were published in 135 journals, with The American Journal of Psychiatry publishing many papers. Papers published in Neuroscience and Bio-Behavioral Reviews had the highest number of citations per paper (n=509.0). Conclusion. The present study suggests that most HCPs have emerged from the United States, are based on funded research, and have involved authors from more than one country. Originality/Value. This study presents significant results, in a more comprehensive manner, related to the high-cited publications (HCPs) on Obsessive-Compulsive Disorder (OCD).